Reciprocal longitudinal effects among Korean young adolescent’ negative peer relationships, social withdrawal, and smartphone dependence - Hye-Sun Lee; Mikyung Choi; Eun-Yeong Na (Heliyon, 2024)
The research should consider the complex dynamics of social interaction to better understand smartphone dependence among adolescents. In social situations, adolescents can choose to interact with their peers or use their smartphones, and smartphone dependence can drive adolescents far away from interaction with their peers. Adolescents, conversely, may use smartphones to avoid peer interaction because they have experienced social withdrawal or negative peer relationships. Previous research has not discussed enough what precedes or follows in longitudinal relationships. This study aims to examine the reciprocal longitudinal effects between adolescents’ negative peer relationships, social withdrawal, and smartphone dependence. The analysis used longitudinal panel data collected yearly between 2018 and 2020 from the Korean Children and Youth Panel Survey (KCYPS) sampled from adolescents in the Republic of Korea and employed autoregressive cross-lagged modeling on 2230 participants. The reciprocal longitudinal relationships differed depending on the sub-factors of smartphone dependence. For instance, the sub-factor of smartphone dependence, including virtual life orientation and withdrawal, had reciprocal longitudinal relationships with negative peer relationships. The other sub-factor of smartphone dependence, including daily life disturbance and tolerance, influenced negative peer relationships consistently, but the converse path did not. In addition, social withdrawal longitudinally affected negative peer relationships the following year. However, the reciprocal longitudinal relationships between social withdrawal and smartphone dependence were not significant in any path in this research. This research provides practical implications for intervention to reduce smartphone dependence among young adolescents.